Caries preventive effect of sugar-substituted chewing gum - Machiulskiene V, Nyvad B, Baelum V. (Blackwell Synergy, 2001)
The aim of this 3-year community intervention trial was to determine the caries preventive effect of sugar-substituted chewing gum among Lithuanian school children, and to assess compliance with the instructions for gum use.